Enhancing Digital Marketing Strategies Using Artificial Intelligence: An Applied Case Study (Comprehensive Journal of Science, 2025)
In light of the rapid digital transformation and increasing market competition, it has become essential to adopt more effective and intelligent digital marketing strategies. This study aims to explore the role of artificial intelligence (AI) in enhancing digital marketing strategies through an applied case study of a company/platform that utilizes AI technologies in its marketing campaigns. Tools such as sentiment analysis, content personalization, and customer behavior prediction were employed to measure their impact on audience engagement and conversion rates. The results showed a significant improvement in marketing performance and increased customer satisfaction, highlighting the importance of integrating AI technologies into future marketing plans. The study recommends adopting predictive and analytical AI tools as a core part of the digital marketing decision-making process.
Keywords: Artificial Intelligence, Digital Marketing, Sentiment Analysis, Personalization, Behavioral Prediction, Recommendation Algorithms, User Experience, Case Study